2004
DOI: 10.1590/s1516-14392004000100019
|View full text |Cite
|
Sign up to set email alerts
|

Simulating steam oxidation of high temperature plant under laboratory conditions: practice and interpretation of data

Abstract: Specimens of ferritic and martensitic steels have been exposed to steam atmospheres at 550 °C using three different experimental procedures. Slight differences in scale growth kinetics were observed but the major differences were in the morphology of the oxide scales that were formed. The microstructures of the scales have been compared with those formed on similar materials during service

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Studies at elevated pressure showed changes in the high temperature corrosion behavior, as reported e.g., for dry air [16], supercritical CO 2 [17][18][19][20][21] or carburizing atmospheres [14,22]. Corrosion issues in steam turbines have initiated research on water vapor-induced oxidation at elevated pressure in static or flowing pure steam [17,[23][24][25][26][27][28]. In these studies, Fe-and Ni-base alloys were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at elevated pressure showed changes in the high temperature corrosion behavior, as reported e.g., for dry air [16], supercritical CO 2 [17][18][19][20][21] or carburizing atmospheres [14,22]. Corrosion issues in steam turbines have initiated research on water vapor-induced oxidation at elevated pressure in static or flowing pure steam [17,[23][24][25][26][27][28]. In these studies, Fe-and Ni-base alloys were tested.…”
Section: Introductionmentioning
confidence: 99%
“…10 Lots of research efforts have, thus, been performed on steam-side oxide scales. However, the fact is that, although the high temperature steam oxidation mechanism has been extensively investigated in the past years, [11][12][13][14][15] there are still lots of issues associated with the mechanical integrity of the steam-side oxide scales that need more research attention. Among these issues, of special interest are the critical failure resistance and the damage mechanism of the oxide scales.…”
mentioning
confidence: 99%
“…The application of these statistics to hot corrosion metal losses are also illustrated in ISO standards . More recently, this statistical approach to corrosion degradation has been used in a range of environments, for example, .…”
Section: Methodsmentioning
confidence: 99%
“…The application of these statistics to hot corrosion metal losses are also illustrated in ISO standards [22,26,27]. More recently, this statistical approach to corrosion degradation has been used in a range of environments, for example, [28,29]. Post-exposure, samples were imaged by a scanning electron microscope (SEM) equipped with energy dispersive X-ray spectroscopy (EDX) to study the microstructural evolution.…”
Section: Image Analysis Techniquementioning
confidence: 99%